Beyond Fetal Immunity: A Systematic Review and Meta-Analysis of the Association Between Antenatal Corticosteroids and Retinopathy of Prematurity - Zeng, Yue; Ge, Ge; Lei, Chunyan; Zhang, Meixia (Frontiers in Pharmacology, 2022)
Background: Retinopathy of prematurity (ROP) is a major cause of childhood blindness. Antenatal corticosteroids (ACS) exposure is known to ameliorate the risk of and mortality of neonatal morbidities. However, the effect of ACS on ROP development is currently unknown. We conducted a meta-analysis with up-to-date evidence to assess the association between ACS exposure and the development of ROP in at-risk preterm infants. Methods: PubMed, EMBASE, Scopus, Web of Science, and the Cochrane Library were systematically searched from inception to May 2021, supplemented with manual search from reference lists. Studies with a control group reporting ROP rate in ACS-exposed infants were included. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated utilizing a random-effects model. The Newcastle-Ottawa Scale was used for assessment of risk of bias in the included studies. Meta-regressions were performed to explore the predictive role of confounders for between-study variance. Results: A total of 63 studies, involving 196,264 infants, were included. Meta-analysis showed ACS exposure was not associated with ROP occurrence (uOR 0.92, 95% CI 0.80–1.07; aOR 0.87, 95% CI 0.7–1.08). Results from extremely immature subgroups revealed significant reduced risks of ROP occurrence in ACS-exposed infants. ACS exposure was associated with significantly lower odds of ROP progression in adjusted analysis (aOR 0.48, 95% CI 0.26–0.89) instead of unadjusted analysis (uOR 0.86, 95% CI 0.68–1.08). Meta-regression showed birth weight and patent ductus arteriosus of the cohort were associated with ROP occurrence, sample size and study design strongly associated with ROP progression in ACS-exposed infants. Conclusion: ACS treatment may decrease, but not prevent, the severity of ROP. Findings from severe ROP should be interpreted with caution owing to limited studies and the possibility of false-positive results. Considering the particular benefits in extremely immature infants, we recommend routine usage of ACS in mothers with threatened delivery to this particular birth cohort to prevent ROP occurrence. Future studies adjusting for major confounders are warranted to mitigate risk of bias in such observational evidence.